Physical fitness and its association with lean mass in Mexican football players - Lagunes Carrasco , José Omar; López García, Ricardo; Enríquez Reyna , María Cristina; Navarro Orocio , Ricardo; Carranza García , Luis Enrique (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to compare fitness test results between playing position groups of college football players and to analyze the association of lean mass percentage with fitness tests. Eighty-seven football players were assessed for lean mass and seven fitness tests. Differences were found between linemen, big skill players and skill players (p ≤ .001) on fitness tests. Negative associations were found for quickness and agility tests (p ≤ .001), and positive associations were found for strength and jumping tests (p ≤ .001) with lean mass. Linemen were the lowest in lean mass and slowest in the physical tests; and skill players represented the highest lean mass values with the best physical test scores.